Sosiaali- ja terveydenhuollon alueellisten palveluketjujen kehittäminen - Friman Susanna; Ikonen Tuija; Eloranta Sini; Suominen Sakari (Sosiaalilääketieteen yhdistys ry, 2022)
Development of regional service pathways in social and health care
In Finland, there are a number of different actors providing social and health care services in the public, private and third sector. Legal regulations stipulate that the methods of collaboration used in quality management and implementation of patient safety must be agreed upon regionally. The importance of regional collaboration is likely to increase when the social and health care reform is implemented. This interview study focused on the state and needs of regional collaboration in three units of one university hospital district and in three municipalities within the same area. The material was collected with semi-structured theme interviews from persons responsible for quality management or its coordination within the organisations. The interviews were analysed with content analysis using material-based methods. The ways of regional collaboration between the social and health care organisations surveyed in the study varied. The informants described collaboration methods and practices used in regional collaboration that differed in terms of scope and degree of systematicality. Participation in national and regional projects and networks as well as development of individual service processes were common. The informants identified joint regional developmental needs, such as a uniform quality management framework, descriptions of client processes, evaluation and development of interface work, increased implementation of a health-promotion approach, supporting the operation of primary health care, and dissemination of information related to patient care via electronic systems. It was noteworthy that the informants recognised the third sector as a key collaboration partner, whereas they ignored the private sector. Neither did they describe endeavors of integrative social and health care. According to the informants, the social and health care service providers shared a common vision and were prepared to respond to the need of increased regional collaboration required by the proposed social and health care reform.
Social and health care services, regional service pathways, quality management